Budi Utomo Pati in the Historiography of Women's Education in the Dutch East Indies - Edy Supratno; Syafi’ul Kholqi; Siti Nur Aisyahtur Hozanah; Iis Isnawati; Arifudin Sirojul Firdaus (Universitas Islam Negeri Raden Intan Lampung, 2026)
Historiography has generally portrayed Budi Utomo as the pioneer of the Indonesian national awakening and a driving force in indigenous education, while its contribution to women's education at the local level has received limited scholarly attention. This study aims to examine the role of Budi Utomo Pati in pioneering indigenous women's education during the Dutch East Indies period. The research employs the historical method, including heuristics, source criticism, interpretation, and historiography, using Verslag Boedi-Oetomo, Dutch colonial newspapers, and colonial records as primary sources. The findings reveal that Budi Utomo Pati not only advocated women's education but also institutionalized it through the establishment of a girls' school, the employment of salaried teachers, community-based financial support, systematic organizational management, and the acquisition of colonial government subsidies. The study further demonstrates that indigenous male elites served as agents of change in expanding women's access to education at the local level. These findings enrich the historiography of women's education by showing that educational emancipation during the colonial period was driven not only by colonial educational policies or female reformers, but also by the initiatives of modern indigenous organizations.